2018
DOI: 10.3389/fimmu.2018.02095
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio vulnificus RtxA Is a Major Factor Driving Inflammatory T Helper Type 17 Cell Responses in vitro and in vivo

Abstract: T helper type 17 (Th17) cells are a subset of pro-inflammatory T helper cells that mediate host defense and pathological inflammation. We have previously reported that host dendritic cells (DCs) infected with Vibrio vulnificus induce Th17 responses through the production of several pro-inflammatory cytokines, including interleukin (IL)-1β and IL-6. V. vulnificus produces RTX toxin (RtxA), an important virulence factor that determines successful pathophysiology. In this study, we investigated the involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The ΔrtxA mutant, which was constructed by deleting 89% of the rtxA structural gene and then inserting a nptI gene cassette conferring resistance to kanamycin into the deleted rtxA , produces no MARTX toxin 14 . The rtxA :: nptI mutant with the insertion of nptI at the 5′-end of rtxA also produces no MARTX toxin 47 . The revertant, in which the rtxA structural gene was restored from the rtxA :: nptI mutation, produces the WT-MARTX toxin 47 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ΔrtxA mutant, which was constructed by deleting 89% of the rtxA structural gene and then inserting a nptI gene cassette conferring resistance to kanamycin into the deleted rtxA , produces no MARTX toxin 14 . The rtxA :: nptI mutant with the insertion of nptI at the 5′-end of rtxA also produces no MARTX toxin 47 . The revertant, in which the rtxA structural gene was restored from the rtxA :: nptI mutation, produces the WT-MARTX toxin 47 .…”
Section: Methodsmentioning
confidence: 99%
“…The rtxA :: nptI mutant with the insertion of nptI at the 5′-end of rtxA also produces no MARTX toxin 47 . The revertant, in which the rtxA structural gene was restored from the rtxA :: nptI mutation, produces the WT-MARTX toxin 47 . To construct the EF-rtxA mutant, the pDS_EF-MARTX 50 , carrying rtxA with the deletion of 34% structural gene encoding effector domains of the MARTX toxin, was conjugally transferred into the V. vulnificus WT and a resulting mutant by the double homologous recombination was screened out.…”
Section: Methodsmentioning
confidence: 99%
“…Mice were orally administered with 200 μl PBS or bacterial suspension containing 5 × 10 7 CFU of 14BME20 for 10 days. Mice were sacrificed and mucosal dendritic cells (MDCs) were isolated from lamina propria of small intestines, as described previously (24). In brief, the small intestines from the PBS- or 14BME20-treated mice ( n = 3) were washed in cold PBS, and feces, fat tissues and Peyer's patches were removed.…”
Section: Methodsmentioning
confidence: 99%
“…Based on its mode of action, the MARTX toxin is essential for V. vulnificus to improve antiphagocytosis, colonization, and dissemination to the bloodstream and other organs, and thereby lethality in mice [32,33]. Also, recent studies further revealed that the expression of the MARTX toxin moderates immune responses of gut epithelial cells but stimulates inflammatory signaling of immune cells [34][35][36].…”
Section: Exotoxinsmentioning
confidence: 99%